2018
DOI: 10.7554/elife.39494
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus VP3 targets MAVS for degradation to inhibit type III interferon expression in intestinal epithelial cells

Abstract: Rotaviruses (RVs), a leading cause of severe diarrhea in young children and many mammalian species, have evolved multiple strategies to counteract the host innate immunity, specifically interferon (IFN) signaling through RV non-structural protein 1 (NSP1). However, whether RV structural components also subvert antiviral response remains under-studied. Here, we found that MAVS, critical for the host RNA sensing pathway upstream of IFN induction, is degraded by the RV RNA methyl- and guanylyl-transferase (VP3) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 75 publications
(129 reference statements)
4
67
0
Order By: Relevance
“…1A, left panel). We found that ACE2 was predominantly expressed in Cd26 + Epcam + Cd44 − Cd45 − mature enterocytes ( 19, 20 ) (Fig. 1A, right panel).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…1A, left panel). We found that ACE2 was predominantly expressed in Cd26 + Epcam + Cd44 − Cd45 − mature enterocytes ( 19, 20 ) (Fig. 1A, right panel).…”
Section: Resultsmentioning
confidence: 87%
“…VSV-SARS-CoV-2-S-GFP and VSV-SARS-CoV-S-GFP were propagated in MA104 cells in T175 flasks and virus sequences can be found in Table S1. Plaque assays were performed in MA104 cells seeded in 6-well plates using an adapted version of the rotavirus plaque assay protocol ( 19 ). TCID50 assays were performed in MA104 cells seeded in flat-bottom 96-well plates using serial dilutions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five-day-old 129/Sv strain suckling mice were obtained from the Greenberg laboratory breeding colony at Stanford University. IECs were isolated from small intestine tissue pooled from two males and one female by EDTA-dithiothreitol extraction method, and cell sorting was performed as previously described (23,59…”
Section: Scrna-seq Analysismentioning
confidence: 99%
“…to increase with repeated infection or immunization (1). However, innate immunity also may contribute to rotavirus disease, and rotaviruses have been shown to antagonize innate signaling pathways using multiple distinct mechanisms (1)(2)(3).…”
mentioning
confidence: 99%